INOVASI PEMBUATAN MINUMAN HERBAL DI KELOMPOK WANITA TANI BAROKAH UNTUK MENINGKATKAN KETERAMPILAN, PEMASARAN DIGITAL, DAN DAYA SAING PRODUK - Suhartini, Suhartini; Padmaningrum, Regina Tutik; Ebdarwati, Lies (Universitas Mataram, 2025)
The Barokah Women Farmers Group (KWT) in Nitiprayan, Bantul, has significant potential in producing herbal drinks made from spices. However, they face challenges related to product quality and variety, unattractive packaging, and limited marketing. Therefore, this activity aims to improve product quality and diversification, enhance packaging design, and expand marketing through social media. The training, conducted on September 13 and 20, 2025, included the creation of new herbal drinks, environmentally friendly packaging, and the application of digital marketing using WhatsApp, Instagram, Facebook, and TikTok. The training results showed that 100% of members were able to produce new products and package them in more attractive designs, with quality improvements achieved by lowering the simplisia heating temperature from 70°C to 50°C. In addition, KWT Barokah now has social media accounts to support the marketing of their products. Pre-test and post-test evaluations showed a 48.5% increase in participants’ skills. Satisfaction surveys indicated that participants were very pleased with the activity and expressed interest in receiving further training and practice on additional topics. The program continues with ongoing mentoring to ensure the effective application of the knowledge gained. It is expected that this activity can increase the competitiveness of KWT Barokah’s products and have a positive impact on the economic welfare of group members.